TDIF regulates auxin accumulation and modulates auxin sensitivity to enhance both adventitious root and lateral root formation in poplar trees. (30th June 2020) - Yue, Jing; Yang, Heyu; Yang, Shaohui; Wang, Jiehua
Abstract: Of six TRACHEARY ELEMENT DIFFERENTIATION INHIBITORY FACTOR (TDIF)-encoding genes in poplar, PtTDIF1 is predominantly expressed in adventitious roots (ARs), and the other five PtTDIFs are preferentially expressed in lateral roots (LRs). Upon auxin application, expression of all PtTDIFs declined in ARs but transiently increased in LRs. Both exogenous TDIF peptides and overexpression of PtTDIFs in poplar positively regulated the initiation and elongation of LRs, and overexpression of PtTDIFs also increased the number of ARs. As visualized by the auxin-responsive marker DR5:GUS, TDIF had differential impacts on the auxin signaling activity in ARs and LRs, which was corroborated by the free indole-3-acetic acid (IAA) measurements in them. Shoot tips of PtTDIF2- and PtTDIFL2- overexpressing (together as PtTDIFs OE ) trees revealed an enhanced IAA biosynthetic capacity, and removal of the aerial tissues dramatically diminished the root phenotypes of micro-propagated PtTDIFs OE trees. Furthermore, PtTDIFs OE poplars displayed an increased sensitivity for exogenous IAA, and N -1-naphthylphthalamic acid (NPA) completely blocked the TDIF-induced AR and LR formation. In PtTDIFs OE roots, several auxin-related LR initiation markers such as GATA23, LBD16 and LBD29 were transcriptionally upregulated, further supporting that TDIF regulates LR organogenesis by strengthening the spatiotemporal auxin cues and that dynamic interplays between hormones govern root branching and developmental plasticity in tree species. Abstract : Highlights By dynamically regulating auxin signaling and polar auxin transport, TDIF strengthens the spatiotemporal auxin cues to promote the formation of adventitious and LR in poplar.